Refugees welcome, but not in my backyard? The impact of immigration on right-wing voting : evidence from Germany - Johannes Jasny; Tilman Becker (IZA Journal of Development and Migration, 2020)
This article studies whether immigration in voter's neighborhoods is a driving factor of the rise of Germany's major right-wing party Alternative fuer Deutschland (AFD) and the decline of Angela Merkel's center ruling party the Christian Democratic Union (CDU). We use the 2015 refugee crisis as a natural experiment to study the short-run impact of refugee presence on the voting behavior in German municipalities. This is the first study to use a spatial econometric framework combining small-scale immigration data, election data, and a set of socioeconomic factors. Our main finding states that the local immigration boosted AFD votes but did not affect CDU votes directly. Instead, in regions that perceived immigration indirectly, that is in neighboring municipalities, the CDU gained fewer votes.
Keywords: H120; J1; J110; J150; 330; Voting behaviour; immigration; unemployment; refugee crisis management; socioeconomic inequality; demographics